Allotment Gardens: A Reflection of History, Heritage, Community and Self - Lesley Acton (Papers from the Institute of Archaeology, 2011)
Allotments are small parcels of rented land, in rural and urban locations, used for growing fruits and vegetables for personal consumption. The demand for allotments and their availability have changed over time. In this article, I focus on the reasons for the changing demand and the motivation behind taking up this activity. In so doing, I refute the long held assumption that allotmenteering was taken up primarily for economic reasons. Instead, I show that while allotments have at various times been used for the alleviation of hunger, it is the social aspect of this hobby that primarily motivates most plot holders. Accordingly, I show the various ways in which allotments are valued both by the individual and the collective, including as part of our history and cultural heritage.
Keywords: gardening; vegetables; allotments